The Development of High-rise Housing Image in Istanbul: Policies and Architectural-is(m)s - Sarı, Tüba; Dulgeroglu, Yurdanur (Yildiz Technical Univ, Fac Architecture, 2019)
In Istanbul, high-rise buildings, which are predominantly located on the axis of Sisli-Maslak, the central business area of the city, and which are mostly formed by business centers and hotels, have become dominant in housing typologies in recent years, creating different urban foci. Within the scope of the research, the different urban foci including Sisli-Maslak, Basaksehir-Beylikduzu, Kozyatagi-Atasehir, Maltepe-Kartal and Historical Peninsula-Walls districts are analyzed by virtue of vertical dense structuring rises in the residential architecture of Istanbul after 2000s. Thus, the attention should be paid to multi-centered development and disintegration of the high-rise housing structures in the Istanbul metropolitan area. The first hypothesis of the study argues that the multicentered development increases with the high-rise buildings are spread throughout the residential structures, which forces urban fabric to the transformation. Considering the limits and the scope of the research, it is aimed to that residential and mixed-use high-rise buildings in five different urban foci in Istanbul, which mainly focused on housing function, in the level of 2025 floors and over are analyzed and synthesized. In accordance with these criteria, the Trump Towers, G Plus, Andromeda Gold, Safi Espadon and the OnaltiDokuz Towers selected according to the Convenience Sampling method are representative examples of five different urban centers in Istanbul. The projects focused on the development of the high-rise housing image in Istanbul are examined in three different contexts such as architectural-aesthetic relations, architectural-urban relations and architectural-presentation relations. Another hypothesis based on the research aims to prove that development of an image-focused architecture with the rise of buildings displaying the search of differentiation, form and image characterizing the city, especially considering the existing construction rate of high-rise buildings in the residential area in recent years.
Keywords: Multi-centered development; urban silhouette; housing; architectural image; high-rise